ANALYZING DIGITAL INNOVATION'S IMPACT ON BATIK MSMES: A BIBLIOMETRIC STUDY OF BATIK MSMES IN GENERAL’S ENTREPRENEURIAL ECOSYSTEM. - Rr Hawik Ervina Indiworo; Nor Hafizah Abdul Rahman; Hazlina Hassan (Universitas PGRI Semarang, 2026)
This study employs bibliometric analysis to investigate the impact of digital innovation on Batik Micro, Small, and Medium Enterprises (MSMEs), with a particular focus on the Batik MSMEs in general Batik Center in , Indonesia. By analyzing scholarly publications from 2015 to 2025, the research maps the evolution of digital innovation in the context of cultural entrepreneurship. A dataset of 366 peer-reviewed articles, sourced from the CrossRef database, was processed using Publish or Perish and VOSviewer software. The findings highlight key thematic clusters, including digital transformation, market expansion, sustainability, and cultural preservation. The study reveals how digital innovation has empowered local MSMEs by enhancing their competitiveness, broadening market reach, and ensuring the preservation of traditional batik craftsmanship. This bibliometric study not only illuminates the development of research on digital innovation in batik entrepreneurship but also identifies emerging trends, research gaps, and opportunities for future studies. The results offer valuable insights for policymakers, scholars, and practitioners aiming to support sustainable digital entrepreneurship in traditional industries.